Demography and fitness of Sesamia inferens Walker (Lepidoptera: Noctuidae) on three important gramineous crops - Chen Li; Zhen Shen; Liang-De Tang; Xi-Ya Wang; Yuan-Qin Huang; Yu-Fei Zhang; Ming-Yue Mu; Guy Smagghe; Lian-Sheng Zang (CABI Agriculture and Bioscience)
Abstract Background Pink stem borer, Sesamia inferens (Walker), a major rice pest, has rarely been reported to cause serious damage to sorghum in China. During a survey of insect pests in glutinous sorghum for Chinese liquor production areas in Guizhou Province, it was found that S. inferens has caused serious damage to local sorghum in recent years. Methods In this context, we assessed the adaptation of S. inferens to three gramineous crop host plants (maize, rice and sorghum) based on age-stage, two-sex life table theory. Results Sesamia inferens had the highest development time, survival rate and total longevity on rice, followed by on sorghum and maize. There was no significant difference in intrinsic rate of increase and finite rate of increase among maize (r = 0.0702 day−1, λ = 1.0727 day−1), sorghum (r = 0.0681 day−1, λ = 1.0705 day−1) and rice (r = 0.0645 day−1, λ = 1.0666 day−1), but the mean generation period (T) was significantly higher for populations reared on rice (53.84 days) than on sorghum (49.53 days) and maize (47.31 days). Conclusions The results of our study indicate that S. inferens was able to complete the full developmental cycle on all three host plants. This study further supports that glutinous sorghum is an adaptable host plant for S. inferens.